UBE2S mediates tumor progression via SOX6/β-Catenin signaling in endometrial cancer. (April 2019) - Lin, Meifang; Lei, Ting; Zheng, Ju; Chen, Shuqin; Du, Liu; Xie, Hongning
Graphical abstract: Highlights: UBE2S overexpression is significantly correlated with poor outcomes in two independent cohorts consisting of 773 patients. UBE2S promotes cell proliferation and migration in EMC. UBE2S exerts oncogenic activities via activation of SOX6/β-Catenin signaling. Abstract: Dysregulation of ubiquitin-conjugating enzyme E2S (UBE2S) contributes to tumor progression. However, its clinical significance and biological function in endometrial cancer (EMC) remain unclear. Here, we show that UBE2S is upregulated in EMC and exhibits oncogenic activities via activation of SOX6/β-Catenin signaling. High expression of UBE2S is significantly associated with poor prognosis in two independent cohorts consisting of a total of 773 patients with EMC. in vitro studies demonstrate that ectopic expression of UBE2S promotes cell proliferation and migration, whereas knockdown of UBE2S results in opposite phenotypes. Overexpression of UBE2S in EMC cells enhances the nuclear translocation of β-Catenin, and subsequently induces the expression of c-Myc and Cyclin D1. Inhibition of β-Catenin by XAV-939 markedly attenuates UBE2S-promoted cell growth. Mechanistically, UBE2S suppresses the expression of SOX6 to trigger β-Catenin signaling. Re-expression of SOX6 in UBE2S-expressing EMC cells abolishes the nuclear localization of β-Catenin. Collectively, these data suggest UBE2S may serve as a promising prognostic factor and function as an oncogene in EMC. The newly identified UBE2S/SOX6/β-Catenin axis represents a new potential therapeutic target for EMC intervention.